Fast and sustainable recycling of epoxy and composites using mixed solvents - Mu, Quanyi; An, Le; Hu, Zhiqiang; Kuang, Xiao (Polymer degradation and stability, 2022)
•The anhydride-cured epoxy resin can be rapidly decomposed by mixed solvent below150°C at normal pressure.•The depolymerized epoxy oligomer and residual solvents were facilely separated by reduced pressure distillation.•Both the epoxy oligomer and solvents were reused for the next round of recycling.•The carbon fiber reinforced epoxy composite can be recycled to reclaim the high-value carbon fiber with unchanged mechanical properties. Chemical recycling of thermosets and composites can reclaim polymer matrix and high-value reinforcement to protect the environment and save resources. However, efficient and sustainable chemical recycling of epoxy thermosets is still a significant challenge, specifically, improving the decomposition rate, easily separating and reusing the decomposed components under mild condition. Herein, we report the fast and sustainable recycling of epoxy and composites by small-molecule assisted bond exchange reaction (BER) in a mixed solvent. The anhydride-cured epoxy resin with embedded catalyst was rapidly decomposed by the mixed solvent containing a high boiling point alcohol and inert good solvent via transesterification below 150°C at normal pressure. The epoxy decomposition rate was optimized by altering the good solvent types and solvents mixing ratios. We found the epoxy decomposition rate was the fastest in dimethylformamide/ethylene glycol (50/50) due to balanced solvent diffusion/swelling and reaction rate. After epoxy decomposition, the depolymerized epoxy oligomer (DEO) and residual solvents were readily separated by reduced pressure distillation below 80°C. The DEO as an additive (up to 20%) was repolymerizated with fresh epoxy resin to make epoxy materials, which showed similar mechanical properties to the original epoxy with slight deterioration even for several recycling cycles. The reclaimed solvent was used for the next round of recycling. With the optimized condition, carbon fiber reinforced epoxy composite was also recycled to reclaim the high-value carbon fiber with unchanged mechanical properties. This work presents a sustainable and fast recycling paradigm for industrial-grade epoxy and composite with potential for upscale engineering applications. [Display omitted]